“Inside the bubble”: a look at the experiences of student-athletes in revenue-producing sports during college and beyond - Menke, Donna J. (Kansas State University, 2010)
This phenomenological study sought to address the overarching research questions: What are the costs and benefits of participation in Division I college sports? How does participation in Division I college sports prepare student-athletes for life after college? A qualitative methodology was selected to provide richer data than that which could be collected via surveys. The researcher interviewed 15 former student-athletes, each of whom participated in either football or men’s basketball at one Division I institution. According to the study participants, having a strong support system, including a career networking system and gaining positive attributes were the benefits of the experience. The heavy time commitment, the perceptions of others outside of athletics, and health challenges were all cited as costs of the experience. For the most part, participants of the study believed their college experience prepared them for life after college by providing career networking opportunities as well as attributes that are valuable in their work and personal lives. Four recommendations for practice were revealed from this study. First, athletic department personnel, campus administrators, and student service unit across campus, should help student-athletes understand and market attributes they are gaining in their roles as athletes and students. Second, campus professionals can help these young adults deal with the negative perceptions and treatment they receive from others on campus. In addition, campus administrators should act to minimize negative stereotypes by speaking out against them and emphasizing the positive examples that are sure to exist on campus. Finally, these professional can learn more about the long-term mental and physical health concerns associated with participation in high-stress, physical college sports and educate participants on preventing or minimizing the potential health consequences of their participation.
Keywords: student-athletes; career; health; skills; Education, Higher (0745)